1976
DOI: 10.1073/pnas.73.5.1749
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for tandem integration of avian myeloblastosis virus DNA with endogenous provirus in leukemic chicken cells.

Abstract: The integration site of avian myeloblastosis virus (AMV) proviral DNA in DNA from leukemic chicken myeloblasts has been studied by three sequential nucleic acid hybridizations that can localize the proviral DNA Preparation of DNA and Reassociation. The methods for isolation of DNA from leukemic myeloblasts, reassociation of DNA, DNA size determination, and separation of singlestranded and double-stranded nucleic acids by hydroxylapatite chromatography have been described (26).Nucleic Acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

1976
1976
1990
1990

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…Such repetitious DNA sequences have been implicated in gene regulation and chromosome structure (15). Also, proviral DNA sequences in normal and transformed chicken cells have been shown to be integrated next to middle repetitious cellular DNA sequences which appear to be nonrandomly interspersed among nonrepetitive sequences in eukaryotes (16,19,20,23,29).…”
mentioning
confidence: 99%
“…Such repetitious DNA sequences have been implicated in gene regulation and chromosome structure (15). Also, proviral DNA sequences in normal and transformed chicken cells have been shown to be integrated next to middle repetitious cellular DNA sequences which appear to be nonrandomly interspersed among nonrepetitive sequences in eukaryotes (16,19,20,23,29).…”
mentioning
confidence: 99%
“…Other authors have shown that certain viruses such as SV40 [31] and polyoma [32] may be integrated in tan dem in the DNA of chronically infected cells, and Shoyab el at. [33] provided evidence that myeloblastosis virus is integrated in tandem with chicken endogenous virus. Tandem trans fections observed here are best explained by the integration of the two parental proviruses into the same integration site or two adjacent or slightly separate sites on the chromosomal DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Melting profiles of the hybrids strongly suggest the presence of heterogeneous closely related sequences [6]. Whether these multiple endogenous viral genomes are localized randomly or in tandem [10] is the next question to be approached.…”
Section: Fig 1 a Hybridization Kinetics O F T-felv 3h-cdna With Framentioning
confidence: 99%